Bacillus pumilus WP8 exhibits biocontrol efficacy against tomato bacterial wilt via attenuation of the virulence of the pathogenic bacterium - Min Shen; Dan Xia; Zhifeng Yin; Qingxin Zhao; Yijun Kang (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science, 2018)
Bacillus pumilus WP8 is a plant growth-promoting rhizobacterium (PGPR) with good biocontrol efficacy against tomato bacterial wilt caused by Ralstonia solanacearum Rs1115. Biocontrol, however, is not due to antagonism of the pathogenic bacterium. Thus, we hypothesised that the biocontrol efficacy of WP8 was achieved by attenuation of Rs1115 virulence. Here, pot experiments for comparison of Rs1115 in different plant parts were conducted to investigate the ability of WP8 to prevent entry of Rs1115 into the regions of the plant above ground. Primary and secondary metabolite contents of WP8 and their inhibitory effects on twitching and swarming motilities of Rs1115 were determined by microscopic examination and crystal violet staining. The effects of WP8 metabolites on the expression of typical virulence genes in Rs1115 were established by quantitative PCR. Rs1115 abundance in the rhizosphere increased with time after inoculation. However, the shoots treated with WP8 were pathogen-free on days 3 and 6 after inoculation. In the WP8 + Rs1115 treatment group, the abundance of Rs1115 in shoots was 1.5 lg units higher on day 9 post-inoculation than that in the Rs1115 treatment group, while less Rs1115 was observed in the leaves. This indicated that WP8 prevented Rs1115 from spreading to the regions of the plant above ground. Furthermore, some heat-resistant secondary metabolites of WP8 (e.g. lipopeptides) inhibited the twitching and swarming motility of Rs1115. Moreover, the metabolites decreased the expression of typical virulence genes in Rs1115. Therefore, WP8 was shown to attenuate Rs1115 virulence, possibly through pumilacidin secretion.